Volunteer police, choosing to serve: exploring, comparing, and assessing volunteer policing in the United States and the United Kingdom - Wolf, Ross (Routledge, 2018)
Introduction: defining volunteer policing -- The impact of volunteer policing -- The utilization and deployment of volunteer police in the UK and USA -- History of volunteer policing -- The contemporary role and functions of volunteer police -- Training volunteer police -- A comparison of USA/UK volunteer policing -- Volunteer policing around the globe -- What the future holds for volunteer policing -- Index